Current status of phosphine resistance in Indian field populations of Tribolium castaneum and its influence on antioxidant enzyme activities - Satyapriya Singh; Suresh M. Nebapure; Sukumar Taria; Doddachowdappa Sagar; Sabtharishi Subramanian (Scientific Reports, 2023)
Abstract Resistance to phosphine is widely reported in several stored product insect pests globally. However, knowledge of its prevalence and the association of antioxidant enzymes with phosphine resistance is limited. Herein, we assessed the levels of phosphine susceptibility and estimated the antioxidant enzyme activities viz., superoxide dismutase (SOD), peroxidase (POX), and catalase (CAT) in selected Indian populations of red flour beetle Tribolium castaneum (Herbst). Dose–response probit assays revealed that the LC50 values ranged from 0.038 to 1.277 mg L−1 showing 2.11 to 70.94-fold resistance to phosphine compared to susceptible check. Activities of antioxidant enzymes varied significantly between the T. castaneum populations following phosphine exposure. The magnitude of SOD activity ranged from 8.77 to18.82 U mg−1 protein, while, the activities of POX and CAT varied between 52.42 and 408.32 and 61.11 to 247.49 µM H2O2 reduced min−1 mg−1 of protein, respectively. The correlation analysis revealed a significant positive association of SOD (r = 0.89) and POX (r = 0.98) with increased resistance ratio, while the CAT (r = − 0.98) is negatively linked with resistance to phosphine. A principal component analysis identified phosphine resistance was closely associated with POX and SOD activities but was unrelated to the CAT activity. Our results throw light on the varied association of antioxidant enzyme activities in response to phosphine fumigation in field populations of T. castaneum. Further studies on the biochemical and molecular basis of phosphine stress in insects may help to devise suitable strategies to safeguard storage commodities and ensure a sustainable environment.